Pyrotechnic robot - constructive design and command - Staretu, Ionel A.; Ionescu, Marius A. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Pyrotechnic robots are service robots used to reduce the time for intervention of pyrotechnic troops and to diminish the danger for the operators. Pyrotechnic robots are used to inspect dangerous areas or/and to remove and to distroy explosive or suspicious devices/objects. These robots can be used to make corridors through mined battle fields, for manipulation and neutralization of unexploded ammunition, for inspection of vehicles, trains, airplanes and buildings. For these robots, a good functional activity is determined with regard to work space dimensions, robotic arm kinematics and gripper characteristics. The paper shows the structural, kinematic, static synthesis and analysis as well as the design and functional simulation of the robotic arm and the grippers attached on the pyrotechnic robot designed by the authors.